Harmonized Alignment in Ethical Leadership: Synthesizing Maimonides’ Rational Allegiance and Dessler’s Giving Paradigm - Hoch, Liron (ETHICS IN PROGRESS, 2025)
This article offers a comparative analysis of leadership paradigms articulated by Maimonides and Rabbi Eliyahu Dessler, emphasizing their enduring relevance to contemporary ethical and organizational leadership. Maimonides’ Dual Allegiance model integrates intellectual rigor, ethical autonomy, and social responsibility into a rational, duty-bound framework. In contrast, Rabbi Dessler’s Giving Paradigm, as presented in Strive for Truth, centers on relational ethics, moral intentionality, and the transformative power of altruistic giving. Despite their differing emphases – cognitive clarity versus emotional insight – both approaches converge in promoting a multidimensional, ethically grounded vision of leadership. This study introduces Harmonized Alignment, a synthesis that balances intellect, empathy, and moral action, grounded in classical Jewish thought. The model offers practical guidance for leaders navigating ethical dilemmas and striving to foster sustainable, value-driven organizational cultures in complex modern environments.